How would i simplify this: (x-1)(x+2)-(x-3)^2

I keel getting -3 -11, but the right answer is 7x - 11

1 answer

x^2 + x - 2 - x^2 + 6x - 9

7 x - 11
Similar Questions
    1. answers icon 1 answer
  1. simplifying square roots1) find volume of this prism? v=bwh b=√12" w=√6" h=√8" 2)simplify: √576 3)simplify: √400
    1. answers icon 3 answers
  2. Simplify the expression.(-4)^-6(-4)^-7 My answer: -4 Simplify and give the answer in scientific notation. (5 X 10^6((3 X 10^5)
    1. answers icon 6 answers
    1. answers icon 1 answer
more similar questions